2009
DOI: 10.1182/blood-2009-01-199497
|View full text |Cite
|
Sign up to set email alerts
|

Pneumoviruses infect eosinophils and elicit MyD88-dependent release of chemoattractant cytokines and interleukin-6

Abstract: Eosinophils are recruited to the lung in response to infection with pneumovirus pathogens and have been associated with both the pathophysiologic sequelae of infection and, more recently, with accelerated virus clearance. Here, we demonstrate that the pneumovirus pathogens, respiratory syncytial virus (RSV) and pneumonia virus of mice (PVM), can infect human and mouse eosinophils, respectively, and that virus infection of eosinophils elicits the release of diseaserelated proinflammatory mediators from eosinoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 59 publications
2
59
0
Order By: Relevance
“…Antiviral effector functions of eosinophils were demonstrated in other viral infections wherein viral burden and mortality were reduced in hypereosinophilic mice (20,36,37), and granule proteins reduced the infectivity of respiratory syncytial virus and PVM (17,18), but not SeV (37). Although virus-induced eosinophil PMD was previously thought to require allergen exposure (20), we show that PMD can occur in response to IAV alone, suggesting eosinophils have the ability to respond to IAV as dynamically as they do to allergens.…”
Section: Discussionmentioning
confidence: 57%
“…Antiviral effector functions of eosinophils were demonstrated in other viral infections wherein viral burden and mortality were reduced in hypereosinophilic mice (20,36,37), and granule proteins reduced the infectivity of respiratory syncytial virus and PVM (17,18), but not SeV (37). Although virus-induced eosinophil PMD was previously thought to require allergen exposure (20), we show that PMD can occur in response to IAV alone, suggesting eosinophils have the ability to respond to IAV as dynamically as they do to allergens.…”
Section: Discussionmentioning
confidence: 57%
“…40 Zimmermann et al 41 compared the ova and Af sensitization challenge models directly to one another via DNA microarray; among the 236 transcripts unique to the Af sensitization and challenge model are those encoding several proinflammatory cytokines, including IL-1b, IL-1a, CCL3, and most notably, IL-6, which has already been shown to have an impact on virus-eosinophil interactions. 42 The precise mechanisms via which Af (but not ova) primes eosinophils to respond to virus infection remain to be explored. Of note, Davoine et al 43 reported that human eosinophils interact with parainfluenza virus and release peroxidase only when in coculture with antigen presenting cells and CD4…”
Section: Discussionmentioning
confidence: 99%
“…Another recent report shows that human eosinophils are targets of RSV infection, can support genome replication, and can release infectious virions (26). This observation raises the important question of where the infection of circulating blood cells may occur, either upon recruitment of mature leukocytes to the peripheral site of infection and inflammation (i.e., the lungs), in the bloodstream during a viremic episode, or rather at some stage of the maturation process within the bone marrow.…”
Section: Discussionmentioning
confidence: 99%